Synthesis, in silico and in vitro antimicrobial efficacy of substituted arylidene-based quinazolin-4(3H)-one motifs - Oduselu, Gbolahan O.; Aderohunmu, Damilola V.; Ajani, Olayinka O.; Elebiju, Oluwadunni F.; Ogunnupebi, Temitope A.; Adebiyi, Ezekiel (Frontiers in Chemistry, 2023)
Introduction: Quinazolin-4(3H)-one derivatives have attracted considerable attention in the pharmacological profiling of therapeutic drug targets. The present article reveals the development of arylidene-based quinazolin-4(3H)-one motifs as potential antimicrobial drug candidates. Methods: The synthetic pathway was initiated through thermal cyclization of acetic anhydride on anthranilic acid to produce 2-methyl-4H-3,1-benzoxazan-4-one 1, which (upon condensation with hydrazine hydrate) gave 3-amino-2-methylquinazolin-4(3H)-one 2. The reaction of intermediate 2 at its amino side arm with various benzaldehyde derivatives furnished the final products, in the form of substituted benzylidene-based quinazolin-4(3H)-one motifs 3a–l, and with thiophene-2-carbaldehyde to afford 3 m. The purified targeted products 3a–m were effectively characterized for structural authentication using physicochemical parameters, microanalytical data, and spectroscopic methods, including IR, UV, and 1H- and 13C-NMR, as well as mass spectral data. The substituted arylidene-based quinazolin-4(3H)-one motifs 3a–m were screened for both in silico and in vitro antimicrobial properties against selected bacteria and fungi. The in silico studies carried out consisted of predicted ADMET screening, molecular docking, and molecular dynamics (MD) simulation studies. Furthermore, in vitro experimental validation was performed using the agar diffusion method, and the standard antibacterial and antifungal drugs used were gentamicin and ketoconazole, respectively. Results and discussion: Most of the compounds possessed good binding affinities according to the molecular docking studies, while MD simulation revealed their levels of structural stability in the protein–ligand complexes. 2-methyl-3-((thiophen-2-ylmethylene)amino) quinazolin-4(3H)-one 3 m emerged as both the most active antibacterial agent (with an minimum inhibitory concentration (MIC) value of 1.95 μg/mL) against Staphylococcus aureus and the most active antifungal agent (with an MIC value of 3.90 μg/mL) against Candida albicans, Aspergillus niger, and Rhizopus nigricans.